Dynamical Model of Axially Moving Steel Strips*. Issue 20 (2016) - Saxinger, M.; Steinboeck, A.; Baumgart, M.; Kugi, A.
Abstract: Axially moving strips are frequently encountered in industry for various applications. On the one hand, accurate models of transverse displacements of strips are desired for plant design and safety or reliability reasons. On the other hand, the models may serve as a basis for model-based controller and observer design. For the latter also, the complexity of the models should be as low as possible. This work focuses on the development of dynamical models of the motion and elastic deformation of axially moving steel strips guided by rolls. For spatial discretization of both in-plane and out-of-plane motion, the Galerkin weighted residual method is employed and the longitudinal direction of the strip is divided into finite elements. A tailored time integration method is implemented and dynamic simulations for different boundary conditions of a strip in a hot dip galvanizing line are carried out and analyzed. The influence of the geometrical nonlinearity on the transversal displacements of the strip is investigated by means of a faulty air cooler. Finally, the affect of the geometrical nonlinearity on the dynamic and static behavior of the steel strip is investigated in more detail.